The regulation of skin homeostasis, repair and the pathogenesis of skin diseases by spatiotemporal activation of epidermal mTOR signaling - Wang, Juan; Cui, Baiping; Chen, Zhongjian; Ding, Xiaolei (Frontiers in Cell and Developmental Biology, 2022)
The epidermis, the outmost layer of the skin, is a stratified squamous epithelium that protects the body from the external world. The epidermis and its appendages need constantly renew themselves and replace the damaged tissues caused by environmental assaults. The mechanistic target of rapamycin (mTOR) signaling is a central controller of cell growth and metabolism that plays a critical role in development, homeostasis and diseases. Recent findings suggest that mTOR signaling is activated in a spatiotemporal and context-dependent manner in the epidermis, coordinating diverse skin homeostatic processes. Dysregulation of mTOR signaling underlies the pathogenesis of skin diseases, including psoriasis and skin cancer. In this review, we discuss the role of epidermal mTOR signaling activity and function in skin, with a focus on skin barrier formation, hair regeneration, wound repair, as well as skin pathological disorders. We propose that fine-tuned control of mTOR signaling is essential for epidermal structural and functional integrity.